2008
DOI: 10.1002/mop.23456
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Fabry‐Perot resonator printed antennas using FSS superstrate with dissimilar size

Abstract: In this article, a new technique is proposed which can handle the singularity problem arising in the MoM solution of the electric field integral equation. The method involves MCI technique in evaluation of the moment matrix elements. One major advantage of the MCI technique is that it removes the singularity problem arising in integration of singular integrand without any analytical modification or approximation to the integrand by only employing the "local correction technique," where the uniformly distribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(40 citation statements)
references
References 11 publications
0
40
0
Order By: Relevance
“…1(b), the load impedance in the transmission line model is imaginary infinity. In [4], it is indicated that the disparities among reflection phases of PRS corresponding to different oblique incident angles up to ±60 • range are small enough to be ignored. Therefore, although PRS shunt susceptance varies with the angle of radiation, for narrow-beam regions of interest, it may be assumed to be constant.…”
Section: Radiation Properties Of Antenna With Pmc Groundmentioning
confidence: 99%
See 2 more Smart Citations
“…1(b), the load impedance in the transmission line model is imaginary infinity. In [4], it is indicated that the disparities among reflection phases of PRS corresponding to different oblique incident angles up to ±60 • range are small enough to be ignored. Therefore, although PRS shunt susceptance varies with the angle of radiation, for narrow-beam regions of interest, it may be assumed to be constant.…”
Section: Radiation Properties Of Antenna With Pmc Groundmentioning
confidence: 99%
“…It essentially provides the benefit of high directivity without requiring the complex network, as the conventional antenna arrays. It has aroused more and more attention [2][3][4] for several years, which results in some interesting conclusions based on different viewpoints and analysis models such as leaky wave model [5][6][7][8][9][10], EBG defect model [11][12][13][14][15][16], FP cavity model [1,2,17,18], equivalent refractive lens model [19,20] have been attained and proposed. A summary of this type of antenna is also presented in [19,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FSS exhibits total reflection or transmission characteristic respectively in the neighborhood of the unit cell resonance. It has been used in many applications, such as radome, sub-reflectors of antenna [1][2][3] and superstrates above patch antenna to enhance the antenna directivity [4,5], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Rectangular loops in slot form are chosen for their dual polarized property and simplicity. The slots have their sides parallel to the edge of patch, lengths 5 and width W. In practical application, various desired operation frequencies can be obtained by adjusting the length of slot and the permittivity of the dielectric substrate. Theoretically, the longer L i (i = 1 ∼ 5) means larger perimeter of the whole slot, which makes the resonant frequency lower.…”
Section: Introductionmentioning
confidence: 99%